Adolfo Maria, da voz na rádio “Angola Combatente” à obra escrita - Almeida, E. C. (Conferência: XV sessão de, 2025)
This text presents a synthetic reading of the political and intellectual journey of Adolfo Maria, an essential figure in Angolan nationalism. From his role as a leading voice and director of the "Angola Combatente" radio station—an MPLA broadcaster based in Brazzaville—to the literary and essayistic production he developed in the post-independence period, Adolfo Maria has established himself as one of the critical consciences of Angolan history. The analysis highlights his ethical coherence, his commitment to historical truth, and the importance of the word (both oral and written) as an instrument of liberation and nation-building. Occurred on October 31, 2025